ANÁLISIS HISTÓRICO DE LOS MOVIMIENTOS SOCIALES FEMENINOS EN RIOBAMBA ENTRE LOS AÑOS 2000 A 2010, VISTOS DESDE LA PRENSA LOCAL - Eras Peña, Norman Vladimir (2020)
The present research paper addresses as main theme, a historical analysis of the female social movements in Riobamba between 2000 and 2010, seen from the local press, taking as reference the "Diario Los Andes". With the review of the archives, it was possible to analyze the participation of these movements in the context, finding the link in the political sphere, in the intellectual production, the participation in the formation of leaders, the demand for spaces for the participation of women and their rights constitutional, participating in the preparation of the constitution of 2008. From the indigenous world there are articles with references to the movement of indigenous women called “MINGA”, presenting themselves as fundamental actors in the construction of spaces for the political participation of women. On the other hand they denote their entrepreneurial and innovative potential looking for alternatives to group and be included in the different social aspects. With the use of historical documents, the corresponding analysis has been established, having among the most important aspects the incursion of the female gender in economics with the creation of projects and workshops carried out so that the rest of the women can strengthen their monetary independence. In politics it is important to include 50% of women on the lists to hold public office and include constitutional reforms. In the social sphere, these movements have sought to adhere to more participants and strengthen their actions, implementing informative workshops so that women know about the new achievements, challenges and rights achieved.